EUSECTRA: European Nuclear Security Training Centre providing hands-on training and education in Nuclear Security and Safeguards - Willem Janssens; Veronique Berthou; Abbas Kamel; Jean Galy; Klaus Luetzenkirchen; Klaus Mayer; Stefan Nonneman (International Journal of Nuclear Security, 2020)
The European Nuclear Security Training Centre (EUSECTRA) inaugurated under this global name about 10 years ago and operated by the European Commission Joint Research Centre (JRC), located both on the Karlsruhe (Germany) and Ispra (Italy) sites, includes a large variety of capacity building and professional development activities which span from the hands-on training for nuclear security and safeguards actors (e.g. respectively border guards or customs and nuclear inspectors) to educational efforts in both nuclear security and safeguards. Whereas the first ones, which gave rise to the new name, focus mainly on detection, on-site assistance, crime-scene management, technical reach-back and nuclear forensics capabilities, the second includes all aspects of nuclear safeguards analytical measurements, containment and surveillance, verification technologies and methodologies etc. This paper provides an overview of the most salient developments in these areas of both technical and academic teaching engagement in the last decade and includes some hints to the potential for enhanced collaboration with the International Nuclear Security Educational Network (INSEN)
Keywords: nuclear security; nuclear safeguards; training centre; education